Criminal Order and its Role in Ending the Criminal Case: Comparative Study - نزال دريد وليد; الحيدري جمال ابراهيم (Journal of Legal Sciences, 2021)
The Criminal Order System is a special procedural system that represents a form of (a non-pleading convention), which is intended to confront a particular type of crime in order to put an end to the expiry of the lawsuit resulting from it in a simple and easy manner that does not observe the rules prescribed for ordinary trials. The basic idea in the system of criminal orders is that the case papers in simple crimes contain enough evidence to decide on them without the need to proceed in the normal way of pleading, confronting and hearing witnesses ... etc.